2019
DOI: 10.1155/2019/4012394
|View full text |Cite
|
Sign up to set email alerts
|

Melittin Inhibition and Eradication Activity for Resistant Polymicrobial Biofilm Isolated from a Dairy Industry after Disinfection

Abstract: The emerging concern about the increase of antibiotic resistance and associated biofilm has encouraged scientists to look for alternative antibiotics such as antimicrobial peptides (AMPs). This study evaluated the ability of melittin to act as an antibacterial biofilm inhibitor and biofilm remover considering isolates from dairy industry. Minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs), minimum biofilm inhibitory concentrations (MBICs), and biofilm removal activities were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The anti-biofilm activities of AMPs are not completely understood. They may affect matrix disruption, binding of DNA, and altering the expression of biofilm-related genes, such as the production of pili, QS systems, cytoplasmic membrane, and flagella assembly or several of these mechanisms ( Park et al, 2014 , Issam et al, 2015 , Galdiero et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-biofilm activities of AMPs are not completely understood. They may affect matrix disruption, binding of DNA, and altering the expression of biofilm-related genes, such as the production of pili, QS systems, cytoplasmic membrane, and flagella assembly or several of these mechanisms ( Park et al, 2014 , Issam et al, 2015 , Galdiero et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the peptidomimetic mPE was able to disrupt the membrane of Candida albicans growing as biofilms (PI uptake) at concentrations 6–12-fold higher (50–100 mg/L) than the MIC vs. planktonic cells (Hua et al, 2010 ). Studies of the activity of AMP vs. polymicrobial biofilms are less frequently reported, but the Herpes simplex-derived AMP gH625-GCGKKKK was able to prevent formation of mixed species biofilms consisting of Candida tropicalis and S. aureus or C. tropicalis and Serratia marcescens as well as eradicating mixed biofilms containing these microbes (de Alteriis et al, 2018 ) as did melittin against a polymicrobial biofilm consisting of selected dairy isolates of bacteria ( P. aeruginosa, Staphylococcus haemolyticus, K. pneumoniae , and Aeromonas caviae ) (Galdiero et al, 2019 ). The de novo AMP ASP-1 was able to eradicate polymicrobial biofilms containing S, aureus, P. aeruginosa, A. baumannii , and K. pneumoniae when formulated into a polyurethane-based dressing (Bayramov et al, 2018 ) and the Komodo dragon-derived peptide DRGN-1 demonstrated moderate eradication activity against mixed biofilms containing P. aeruginosa and S. aureus (Chung et al, 2017 ).…”
Section: Antimicrobial Susceptibility Testing Of Ampmentioning
confidence: 99%
“…A previously described biofilm assay was performed to assess biofilm formation by examined strains, in 96-well polystyrene plates according to Stepanović et al [33,34].…”
Section: Mono-and Dual-species Biofilm: In Vitro Static Modelmentioning
confidence: 99%